Ventilated façade solutions. Issue 1 (1st April 2022) - Baciu, I-R; Isopescu, D N; Lupu, M L; Maxineasa, S G; Pruna, L; Dan, S
Abstract: Reducing the energy consumption needed for creating suitable indoor conditions has become a significant issue on a global scale. The building's envelope and service systems have the most important influence over the amount of energy consumed. This aspect is related to reducing the heat flux across the building envelope in summer conditions and preventing the condensation and infiltration risk in the winter period. The research regarding ventilated façades has advanced taking into account these advantages, which emphasized the need to study and create constructive solutions adapted to the conditions. In this context, this paper represents a brief introduction to ventilated façades solutions, taking into account the definition, their characteristics, the principal constructive elements, the main types of ventilated facades, and last, but not least, their advantages and disadvantages. The authors believe that the study is critical in fully comprehending the characteristics of these systems and their primary components, as well as designing and implementing them in accordance with current environmental needs. It is anticipated that comprehending this concept, as well as its evolution and trends, can contribute in the resolving of a number of ecological and societal issues.